Providing Structural Model Variables Related to Job Satisfaction of Faculty Members of Shiraz University of Medical Sciences - GR Jamali; Abedineftekhari (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: Understanding the factors that create job satisfaction can increase it and motivate faculty to engage in research. This study aims to research into these factors. Materials and Methods:214 faculty members working at SUMS were selected randomly. Data was collected and analyzed. Results: A meaningful relationship between the predictor variables (management support, subjective norm and job security) and job satisfaction was found. The mediator (self efficacy) also showed a significant correlation with the criterion variable (job satisfaction). The results showed that the predictive path analysis (management support, subjective norm and job security) and significant indirect effect through the mediator (self efficacy) with job satisfaction. Conclusion: Too many variables affect job satisfaction of faculty members, some of which were examined. The results of the analysis show that occupational safety and efficacy to the most effective use of the criterion variable of job satisfaction are significant.